Efektivitas Penggunaan Media Pembelajaran Bola Voli Berbasis Web Di SMA Negeri 1 Indralaya Utara - Pratama, Okky Putra Alwin; Destriani, Destriani; Destriana, Destriana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research evaluates the effectiveness of using the D'Volleyball Learning website to learn volleyball at SMA Negeri 1 Indralaya Utara. Using the Classroom Action Research (PTK) method with two action cycles, this research involves instruments such as knowledge tests, lower service skills assessments, and attitude assessments. Data collection techniques include tests, observation, and documentation, with analysis based on learning completeness. The research subjects were 21 students in class XII.IPS.2, consisting of 11 men and 10 women. The results of the cycle I showed knowledge completeness of 42.9% with an average score of 69.4, bottom serve skill at 52.3% with an average of 59, and attitude of 42.9% with an average of 60.2, resulting in an overall average of 46% in the sufficient category. In cycle II, knowledge completeness increased to 85.7% with an average of 88; bottom serve skills to 80.9% with an average of 76.6; and attitude to 85.8% with an average of 80.5, resulting in an overall average of 84.1% in the outstanding category. In addition, student activity increased from 71.3% (active) in cycle I to 80.6% (very active) in cycle II. In conclusion, using the D'Volleyball Learning website has proven effective in improving volleyball learning at SMA Negeri 1 Indralaya Utara. Keywords: Effectiveness, D'Volleyball Learning, Web Based Learning Media,